Integrating local wisdom into EFL reading materials: A needs analysis of vocational students in Eastern Indonesia - Sukun, Dwi Sri Julianie; Fatsah, Hasanuddin; Ibrahim, Moh Syahrun; Miolo, Sartin T.; Katili, Adriansyah Abu; Mukadji, Muziatun (LP2M IAIN Sultan Amai Gorontalo, 2026)
Background: Vocational students often struggle to understand English texts that are complex and not related to their daily lives. In Eastern Indonesia, the lack of culturally relevant materials can reduce engagement and comprehension. Integrating local wisdom into reading materials can bridge this gap by connecting learning with students’ experiences, supported by schema theory and culturally responsive pedagogy. Aims: This study aimed to identify vocational students’ needs for English reading materials incorporating local wisdom in Banggai Laut, Central Sulawesi, and to examine how cultural elements relate to students’ reading challenges, learning needs, and preferences. Methods: This study employed a descriptive quantitative approach using a descriptive survey design within a needs analysis framework. The analysis of target needs (lacks, needs, and wants) was informed by Hutchinson and Waters, while learning needs (input, procedures, teacher roles, learner roles, and settings) were based on Nunan. Twenty students from SMK Al-Hajar and SMK Negeri 2 Banggai participated during the 2024/2025 academic year. Data were collected through a 33-item Likert-scale online questionnaire. The data were analyzed using mean scores and percentages to identify dominant response patterns. Results: The findings revealed that students experienced difficulties with complex sentence structures, technical vocabulary, and factual texts lacking cultural relevance. They reported strong needs for vocabulary support, culturally familiar topics, visual aids, and teacher guidance. Students preferred reading materials related to local folktales, coastal life, traditions, and regional history, and favored activities such as independent reading, small-group discussion, summarizing, highlighting keywords, and strategy modeling. Implications: Mapping students’ target and learning needs prior to material development is essential for vocational contexts. Incorporating local wisdom can support more engaging, comprehensible, and contextually relevant English learning aligned with students’ cultural backgrounds.